37.6k views
2 votes
Simplify 5/8x -2y +3/4x-8y

1 Answer

1 vote

Answer:

On simplification,
(5)/(8)x - 2y + (3)/(4)x -8y   =   ((11)/(8)) x - 10y

Explanation:

Here, the given expression is:


(5)/(8)x - 2y + (3)/(4)x -8y

Now, we can perform operations only on LIKE TERMS,

So, in this expression, separate the like terms we get:


(5)/(8)x - 2y + (3)/(4)x -8y  =  (5)/(8)x +  (3)/(4)x - 2y -8y\\= ((5)/(8) +  (3)/(4))x -(2y + 8y)  = ((5 + 3(2))/(8)) x - (10y)\\= ((11)/(8)) x - 10y\\\implies  (5)/(8)x - 2y + (3)/(4)x -8y   =   ((11)/(8)) x - 10y

Hence, on simplification,
(5)/(8)x - 2y + (3)/(4)x -8y   =   ((11)/(8)) x - 10y

User Avner Solomon
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.